1999
DOI: 10.1557/proc-564-429
|View full text |Cite
|
Sign up to set email alerts
|

Electroplated Cu Recrystallization in Damascene Structures at Elevated Temperatures

Abstract: Transformations in electroplated Cu films from a fine to course grain crystal structure (average grain sizes went from ∼0.1 µm to several microns) were observed to strongly depend on film thickness and geometry. Thinner films underwent much slower transformations than thicker ones. A model is proposed which explains the difference in transformation rates in terms of the physical constraint experienced by the film since grain growth in thinner films is limited by film thickness. Geometrical constraints imposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…A similar thickness dependence of the selfannealing kinetics has been observed previously. 6,7,[24][25][26][27] Supported by the observation of even slower kinetics observed for Cu deposited in damascene trenches, 8,28,29 the thickness dependence has been attributed to geometrical constraints due to trench and via structures and/or the interface and surface of the film. 8 This, however, does not explain the complete absence of self-annealing in the thinnest Cu layer, as observed in the present study, since the as-deposited crystallite sizes are considerably smaller than the layer thickness.…”
Section: B Kinetics Of Self-annealingmentioning
confidence: 99%
“…A similar thickness dependence of the selfannealing kinetics has been observed previously. 6,7,[24][25][26][27] Supported by the observation of even slower kinetics observed for Cu deposited in damascene trenches, 8,28,29 the thickness dependence has been attributed to geometrical constraints due to trench and via structures and/or the interface and surface of the film. 8 This, however, does not explain the complete absence of self-annealing in the thinnest Cu layer, as observed in the present study, since the as-deposited crystallite sizes are considerably smaller than the layer thickness.…”
Section: B Kinetics Of Self-annealingmentioning
confidence: 99%
“…Although this behaviour of electroplated copper is intriguing, the kinetics are hard to study, since the as-deposited grain structure and impurity content of the film strongly depend on the electroplating bath chemistry. Several research groups have reported that the resistivity of as-deposited electroplated copper exceeds the bulk value of 1.67µΩcm by 10-30%, but after a transient period of hours at room temperature, the resistivity decreases to near-bulk values [90][91][92][93][94][95]. The observed sheet resistance decline during self-annealing is attributed to the elimination of electron scattering at the grain boundaries due to the reducing number of grain boundaries as grain growth proceeds.…”
Section: Self-annealing In Electroplated and Sputtered Copper Filmsmentioning
confidence: 99%
“…Dramatic changes in preferred grain orientations were observed for Cu layers over a period of hours or weeks after electrochemical deposition. [3][4][5] Consequently, the properties of Cu electrodeposits, applied e.g., as interconnect lines in microelectronics, change due to the course of self-annealing; a decrease of internal stress level 6 and microhardness 7,8 as well as electrical resistivity 6,9,10 have been reported. A direct comparison of crystallographic texture of electrodeposits reported in the literature is difficult, if possible at all, because the interaction between very different electrolyte compositions and deposition parameters as well as the extent of self-annealing has to be considered.…”
mentioning
confidence: 99%